Monoatomic-thick graphitic carbon nitride dots on graphene sheets as an efficient catalyst in the oxygen reduction reaction. Issue 7 (21st January 2015) - Wang, Xiaopeng; Wang, Lixia; Zhao, Fei; Hu, Chuangang; Zhao, Yang; Zhang, Zhipan; Chen, Shilu; Shi, Gaoquan; Qu, Liangti
Abstract : Monoatomic-thick graphitic carbon nitride dots on graphene sheets rival the electrocatalytic activity of the commercial Pt/C catalyst in the oxygen reduction reaction. Abstract : Atomically thick two-dimensional materials have been increasingly attracting research interest not only due to their promising applications in a range of functional devices but also to their theoretical value to unraveling the catalytic electron transfer process within a simplified scenario. In this work, the monoatomic-thick dot-sized graphitic carbon nitride (g-C3 N4 ) has been synthesized and intimately contacted to the basal plane of the graphene sheet to form the monolayer g-C3 N4 dots@graphene (MTCG). The electrocatalytic activity of the MTCG in the oxygen reduction reaction is found to rival that of the commercial Pt/C catalyst in terms of the catalytic current density and half-wave potential. The density functional theory calculations confirm the catalytic improvement of the MTCG originates from a higher efficiency for the reduction of OOH − than that of the g-C3 N4 alone; therefore, the current work is expected to provide new insights in developing next-generation, highly efficient catalysts for the oxygen reduction reaction.